2016
DOI: 10.1016/j.ejso.2016.06.399
|View full text |Cite
|
Sign up to set email alerts
|

Treatment efficacy with electrochemotherapy: A multi-institutional prospective observational study on 376 patients with superficial tumors

Abstract: ECT represents a valuable skin-directed therapy across a range of malignancies. The most frequently applied treatment modality is intravenous chemotherapy under sedation. Small tumor size predicts durable tumor control, fewer side-effects and better PROs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 34 publications
8
86
0
9
Order By: Relevance
“…In a large international prospectively registry, we identified 57 ECT patients who were administered reduced BLM doses and analysed their outcomes. In this cohort, tumour response data (per‐tumour ORR, 84% and per‐patient ORR, 80%) are in agreement with results achieved by administering the standard BLM dose, as reported in the most recent ECT experiences …”
Section: Discussionsupporting
confidence: 88%
“…In a large international prospectively registry, we identified 57 ECT patients who were administered reduced BLM doses and analysed their outcomes. In this cohort, tumour response data (per‐tumour ORR, 84% and per‐patient ORR, 80%) are in agreement with results achieved by administering the standard BLM dose, as reported in the most recent ECT experiences …”
Section: Discussionsupporting
confidence: 88%
“…A recent meta-analysis assessing 47 prospective studies on patients with cutaneous metastases—mainly from melanoma and breast cancer—treated by skin-directed therapies (including ECT, radiation, photodynamic, intralesional and topical therapies) showed sustained response rates across treatments with G ≥ 3 dermatological toxicity in less than 6% of patients [26]. More recently, a European and an Italian multicenter studies (both adopting the ESOPE protocol), have reported CR rates of 91 and 66.7%, respectively, in BCC patients, although with a short follow-up (6 and 13.9 months, respectively) [10, 11]. In 2016, Rotunno et al reported a 75% CR rate in patients with head and neck BCC treated by ECT.…”
Section: Discussionmentioning
confidence: 99%
“…It included BCC-specific parameters (histological subtypes, tumor borders, ulceration) in order to personalize treatment indication. It was conducted at a center, which is long acquainted with the procedure [8, 9, 11, 39]. Finally, it has a relatively long follow-up, which is crucial for assessing late recurrences [28, 43].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated the safety and efficacy of ECT in the tumor control of a wide range of primary and metastatic malignancies 68,13. In particular, ECT has been shown to be a safe and effective treatment option in a palliative setting for melanoma cutaneous and subcutaneous metastases 1416.…”
Section: Discussionmentioning
confidence: 99%